Genetic susceptibility for cow's milk allergy in Dutch children: the start of the allergic march?. Issue 1 (3rd March 2016) - Henneman, Peter; Petrus, Nicole C. M.; Venema, Andrea; van Sinderen, Femke; van der Lip, Karin; Hennekam, Raoul C.; Mannens, Marcel; Sprikkelman, Aline B.
Abstract: Background: Cow's milk allergy (CMA) is the most common allergic disease in infancy. It is not clear, whether infants with CMA have an increased risk of developing other allergic diseases later in life, the so‐called "allergic march". We aimed to detect genetic associations of CMA using reported single nucleotide polymorphisms (SNP) in other allergic diseases and genetic mutations within the filaggrin ( FLG ) gene. Both to investigate possible causes of CMA, which also suggests an "allergic march". Methods: Thirty children from the Dutch EuroPrevall birth cohort study with CMA in infancy and twenty‐three healthy controls were studied. Six candidate SNPs were selected (minor allele frequency 10–50 % combined with a large effect) based on the literature. Thirteen FLG candidate mutations were selected spread over repeats 1, 3, 4, 5, 6, 7, 9 and 10 respectively. Results: We found two SNP's, rs17616434 (P = 0.002) and rs2069772 (P = 0.038), significantly associated with CMA. One is located near the toll like receptor 6 ( TLR6) gene, which functionally interacts with toll‐like receptor 2, and is associated with an increased risk of other allergic diseases. One is located at the Interleukin 2 ( IL2 ) locus. Twelve FLG amplicons were analyzed, but showed no significant enrichment. Nevertheless, we did observe more FLG mutations in the CMA‐group compared to controls. Conclusion: We significantly associated two SNPs with CMA, suggesting that variation in the TLR6 and IL2 genes contribute to the expression of CMA. In addition, since TLR6 and IL2 were earlier associated with other later onset allergies, this also favours the "allergic march" hypothesis. We observed more FLG mutations in the CMA‐group, albeit we found no statistical significant enrichment of FLG mutations. Further studies are necessary to investigate the role of common variants and FLG or other skin barrier gene mutations in CMA.